Proof of concept pilot study to assess the utility of magnetic resonance extra-cellular volume quantification to diagnose advanced liver disease in people with Cystic Fibrosis. - Daniel H Tewkesbury; Jennifer A Scott; Rowland J Bright-Thomas; Sue Liong; Josephine Naish; Velauthan Rudralingam; Karen Piper Hanley; Andrew M Jones; Varinder S Athwal (PLoS ONE)
Background Current diagnostic tools are limited in their ability to diagnose cystic fibrosis liver disease (CFLD) as disease is often focal in nature. Magnetic resonance extracellular volume quantification (MRI ECV) in the liver may have diagnostic utility in CFLD as a more selective liver volume is assessed and can be performed using equipment readily available in clinical practice on a standard MRI protocol. Methods Healthy volunteers (HV), CF participants with no liver disease (CF-noLD) and CF participants with cirrhosis (CF-C) aged 18 years and above had MRI ECV measured using a 3T Siemens scanner. An additional retrospective analysis was performed to calculate MRI ECV in individuals who had available images obtained using a 1.5T Siemens scanner from a previous study. Results 16 individuals had MRI ECV measured using a 3T Siemens scanner. Mean (SD) MRI ECV was 0.316 (0.058) for HV (n  =  5), 0.297 (0.034) for CF-noLD (n  =  5) and 0.388 (0.067) for CF-C (n  = 6 ). Post-hoc analysis showed a significant difference between CF-noLD and CF-C (p  =  0.046). Of 18 individuals with available images using a 1.5T scanner, mean (SD) MRI ECV was 0.269 (0.048) in HV (n  =  8), 0.310 (0.037) in CF-noLD (n  =  8) and 0.362 (0.063) in CF-C (n  =  2). Conclusions Liver MRI ECV quantification was feasible in adults with CF with no significant difference in results between 1.5T and 3T obtained images suggesting applicability across different types of MRI scanner. A higher MRI ECV was demonstrated in CF participants with cirrhosis suggesting potential utility as a diagnostic tool for those with advanced CFLD. Further evaluation in larger cohorts is warranted.